Facile Synthetic Access Towards Sulfur- and Selenium-Functionalized Boron-Based Multiresonance TADF Emitters - Zeynep Güven; Hadi Dolati; Leo Wessel; René Frank (Molecules)
Thermally activated delayed fluorescence (TADF) materials with high photoluminescence quantum yields and a fast reverse intersystem crossing (RISC) are of the highest interest for organic light-emitting diodes (OLEDs). In the past decade, triaryl boranes with multiple resonance effect (MR) have captured significant attention. The efficiency of MR-TADF emitters strongly depends on small singlet–triplet energy gaps (ΔEST), but also on large reverse intersystem crossing (RISC) rate constants (kRISC). The latter effect has strongly been focused on very recently and has drawn attention to heavier elements, including sulfur and selenium, the large spin–orbit coupling (SOC) of which accelerates RISC effects. Within the context of MR-TADF emitters, the 5,9-X2-13b-boranaphtho [3,2,1-de]anthracene scaffold (X-B-X, X = donor heteroatom, e.g., N, O, S, Se) has been recognized as a promising narrowband-emissive TADF material. However, the incorporation of sulfur and selenium as highly SOC-inducing elements has proven to be difficult. Most synthetic strategies apply protocols initially suggested by Hatakeyama to obtain nitrogen- and oxygen-doped materials. We present an alternative route over the established methodology, which affords highly sought-after sulfur- and selenium-doped materials with a high yield and purity.